3l-6+2l=-2+l

Simple and best practice solution for 3l-6+2l=-2+l equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3l-6+2l=-2+l equation:


Simplifying
3l + -6 + 2l = -2 + l

Reorder the terms:
-6 + 3l + 2l = -2 + l

Combine like terms: 3l + 2l = 5l
-6 + 5l = -2 + l

Solving
-6 + 5l = -2 + l

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-1l' to each side of the equation.
-6 + 5l + -1l = -2 + l + -1l

Combine like terms: 5l + -1l = 4l
-6 + 4l = -2 + l + -1l

Combine like terms: l + -1l = 0
-6 + 4l = -2 + 0
-6 + 4l = -2

Add '6' to each side of the equation.
-6 + 6 + 4l = -2 + 6

Combine like terms: -6 + 6 = 0
0 + 4l = -2 + 6
4l = -2 + 6

Combine like terms: -2 + 6 = 4
4l = 4

Divide each side by '4'.
l = 1

Simplifying
l = 1

See similar equations:

| 6i/5+3i= | | [2x-2]=6 | | 5y=7x+2 | | 189=9-9x | | -(0.79k+0.227)=-(2.09k+0.838) | | 6/4+6i= | | p^3(e^5p-7)-(6p/2_p^2) | | lnx+2=7+lnx-1 | | lnx^3=7lnx | | 5/7×3/4=? | | 4i/8+2i= | | -2x+2=5y | | (2x-1/3)^2 | | 1/3(9h*h-6h) | | 9x/2-10x=7 | | 3(2x+1)+4=24 | | 7x^2-48x+7=0 | | 1/2-1/8=? | | 17-p=7p-13 | | 2x^5-18x^3-2x^2+18=0 | | ln(x+2)=7+ln(x-1) | | 5/12=K-1/3 | | 3n-8(8-8n)=338 | | 3p=-2/3 | | 500=300x+200 | | y=4x^2+24-7 | | 4tan^2x-3=1 | | 6x+3=2x | | 2-(7x+15)=13-3x | | 4(x-3)=10x+24 | | x/y=13/5 | | 14x+6=2(5+7)-4 |

Equations solver categories